Savoring Interventions Increase Positive Emotions After a Social-Evaluative Hassle - Klibert, Jeffrey J.; Sturz, Bradley R.; LeLeux-LaBarge, Kayla; Hatton, Arthur; Smalley, K. Bryant; Warren, Jacob C. (Frontiers in Psychology, 2022)
Achieving a high quality of life is dependent upon how individuals face adversity. Positive psychological interventions are well-suited to support coping efforts; however, experimental research is limited. The purpose of the current research was to examine whether different savoring interventions could increase important coping resources (i.e., positive emotions) in response to a social-evaluative hassle. We completed an experimental mixed subject design study with a university student sample. All participants completed a hassle induction task and were then randomly assigned into different intervention groups. Positive emotion ratings were collected at three points in time (baseline, post induction task, post intervention). Results revealed a significant time x intervention interaction effect, such that individuals in the savoring the moment intervention reported higher levels of positive emotions (at time 3) compared to individuals assigned to the true control group, guided imagery control group, and savoring through reminiscence intervention. Such findings represent a significant extension to savoring theory and offer support for savoring the moment exercises as a primary prevention strategy to bolster effective responses to social-evaluative hassles.